Fluorescent signatures of autochthonous dissolved organic matter production in Siberian shelf seas - Drozdova, Anastasia N.; Krylov, Ivan N.; Nedospasov, Andrey A.; Arashkevich, Elena G.; Labutin, Timur A. (Frontiers in Marine Science, 2022)
The East Siberian Sea is an area of high biogeochemical activity caused by multiple factors, such as an influence of river runoff, Atlantic, and Pacific waters, formation and melting of sea ice, and internal circulation. Extensive amounts of carbon are accumulated in sub-sea permafrost within the Arctic shelf in East Siberia. Thawing permafrost and resulting microbial decomposition of frozen carbon pool is a potential feedback process affected global climate dynamics. Several studies of dissolved organic carbon (DOC) distribution in the East Siberian Sea have demonstrated untypical for other Arctic shelf seas pronounced non-conservative DOC behavior. Using seawater samples from the 69th cruise of R/V Akademik Mstislav Keldysh conducted in the Laptev and East Siberian seas in September 2017, this study examines the distribution of fluorescent dissolved organic matter (FDOM) along the shelf-crossing transects including the areas affected by the Khatanga, Lena, Indigirka, and Kolyma river runoff. The set of 137 excitation-emission matrices (EEMs), analyzed with Parallel Factor analysis (PARAFAC), was described by a 4-component model demonstrating Tucker’s congruence coefficient above the 0.95 threshold. Spectral characteristics of the resulting components allowed identifying them as well-known humic-like A and C, protein-like B/T, and marine humic-like M fluorophores. Component C1 (A fluorophore) showed a good correlation with salinity for different river plume influenced regions. As well as chromophoric DOM (CDOM) absorption, it can be used as marker of input of terrestrial DOM to the Arctic Ocean. A distinctive feature of the East Siberian Sea shelf waters in comparison with the Laptev Sea is the higher content of the C2 and C4 components, exhibiting protein-like and marine humic-like fluorescence. Component C3 (C fluorophore) which is usually identified as terrestrial-derived material, was found to be produced locally on the East Siberian Sea shelf and in the continental slope region of the Khatanga transect. Destruction of dead algae cells, production of marine biota and dissolved organic matter (DOM) reworking are considered as possible autochthonous FDOM sources in the Siberian shelf seas.